2023
DOI: 10.3390/agronomy13051224
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Lamiaceae Species: Bio-Guided Isolation of Active Metabolites from Salvia officinalis L.

Abstract: Lamiaceae family includes various medicinal and aromatic plants used in cosmetics and pharmaceutical industries. The present study aimed to investigate in vitro the cytotoxic, photoprotective and antioxidant activities of ten Lamiaceae taxa; Melissa officinalis subsp. altissima (Sm.) Arcang., Rosmarinus officinalis L., Salvia officinalis L., Sideritis cypria Post, S. euboea Heldr., S. perfoliata L. subsp. perfoliata, S. scardica Griseb., S. sipylea Boiss., Stachys iva Griseb., and Thymus vulgaris L. The aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The collection provides insights on the plant extracts and natural compound composition and their role in human health by inhibiting scavenging reactive oxygen species (ROS), stimulating the production of melanin, and absorbing UV radiation. Tsitsigianni et al [6] investigated the biological activities of different extracts/infusions from ten Lamiaceae species with a rich phytochemical profile, exploring the cytotoxic, photoprotective, antioxidant, and wound-healing properties of different compounds. In that study, five compounds were isolated and identified through NMR spectra, namely salvianic acid A, rosmarinic acid, salvianolic acid K, luteolin-3-O-D-glucuronide, and hispidulin-7-O-D-glucuronide, introducing their photoprotective and non-cytotoxic roles as well as providing a better insight into Salvia officinalis and its bioactive constituents.…”
mentioning
confidence: 99%
“…The collection provides insights on the plant extracts and natural compound composition and their role in human health by inhibiting scavenging reactive oxygen species (ROS), stimulating the production of melanin, and absorbing UV radiation. Tsitsigianni et al [6] investigated the biological activities of different extracts/infusions from ten Lamiaceae species with a rich phytochemical profile, exploring the cytotoxic, photoprotective, antioxidant, and wound-healing properties of different compounds. In that study, five compounds were isolated and identified through NMR spectra, namely salvianic acid A, rosmarinic acid, salvianolic acid K, luteolin-3-O-D-glucuronide, and hispidulin-7-O-D-glucuronide, introducing their photoprotective and non-cytotoxic roles as well as providing a better insight into Salvia officinalis and its bioactive constituents.…”
mentioning
confidence: 99%